Linkages Between Hrm Practices and Firm Performance: The Importance of Talent Management in Achieving Global Competitive Advantage (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Developing a talented workforce is essential tosustainable competitive advantage. Hence, a company that creates a talentedworkforce and implements suitable quality service programs is likely to succeedin a globally competitive economy (Kundu and Vora, 2004). Organizations areparticipants in talent wars in which rewards go to those companies who canattract, develop, use, and retain talent globally (Brake, 2005).